Design of Vehicle Asset Management Information System ( Case Study: STMIK STIKOM Bali ) - I Made Dwi Ardiada; Ni Putu Sri Merta Suryani; Ni Wayan Sri Aryani (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2017)
Vehicle is a transportation asset that many owned by agencies or companies as one of the media operational. Determined operators manage vehicle assets in an agency that becomes a factor of management to be less effective and efficient. In addition, the process is still running conventionally. In the existing business process in STMIK STIKOM Bali is divided into three processes that include the process of borrowing vehicles, operational process, vehicle maintenance process. In this paper we discuss the design of vehicle asset management information system on STMIK STIKOM Bali. The design of this proposed system will be web based using PIECES analysis. Vehicle tracking and reminder system on vehicle asset management becomes one of the features in this system design. For system development using System Development Life Cycle method. This system is expected to facilitate various difficulties either experienced operator or applicant. In addition, this system is expected to reduce the problems regarding the management of vehicle assets.